Mental health care for helpers: Experiences from a training programme - Ajduković, Marina (Array, 1998)
The training program aimed at meeting the mental health needs of care-providers is described. Its goal was to develop and implement a training program for self-management and self-empowerment of care-providers in order to prevent their burnout and vicarious traumatization. In 1994 the practical assistance was provided to 57 helpers in two three-day workshops ; a manual was prepared and the program evaluated. Three groups of stressors were identified by the participants. One group was dependent upon the personality, another group comprised environmental stressors, and the third group included specific characteristics of the helping work. The quantitative and qualitative evaluation model was used which showed that the program met the existing needs of the care-providers. The participants reported improved relations with their collaborators, greater capacity for defining their boundaries at work, less exhaustion and improved communication patterns among the working team members.